The importance of communication and teamwork training for employee performance in hotel industry / Nurul Afiqa Misbah - Misbah, Nurul Afiqa (2021)
This study aims to investigate the importance of communication and teamwork skill training to improve employee performance. For this study, to collect data, the researcher uses secondary data which is from a previous article about communication and teamwork. Types of secondary data that are used are articles, journals, and websites article. Types of communication skill that has been discussed are verbal and non-verbal communication. While the type of teamwork skill to improve employee performance are by providing education to the team member in classroom style, by doing workshop style and simulation training. The research design for this study is an argumentative study. This study is a guideline for the researcher to do for findings. This study is needed to support the issue and finding a good result. In order to get an up-to-date article, the researcher used google scholar and sort it by the latest year. It is sort from 2006 to 2020. Types of a website that the researcher used to find articles are Google Scholar, Scopus, and Google. For the result of the finding, the researcher found that these two types of skill training are important and relate to each other. These two types of training also have a significant relationship with employee performance.